Examining the Impact of Software Testing Practices on Software Quality in Batam Software Houses - Suwarno; Syaeful Anas Aklani; Nellsen Purwandi (P3M Politeknik Negeri Bengkalis, 2025)
This research aimed to investigate the impact of software testing practices on software quality in software companies in Batam, Indonesia. It focused on identifying key factors such as software testing knowledge, software testing approach, and software testing complexity and analysing their correlation with software quality. Data was collected from 48 respondents, including project managers, developers, and QA teams, using a questionnaire distributed via Google Forms and convenience sampling. The questionnaire was designed based on related studies to ensure relevance to the respondents’ roles. Regression analysis identified significant impacts of testing complexity, approach (p = 0.000), and knowledge (p = 0.003) on software quality. The F-test result (F = 32.622) confirmed a strong relationship between testing practices and software quality. These findings emphasise the critical role of robust testing strategies in enhancing software quality. For companies in Batam, the study offers actionable insights, including adopting structured frameworks and preferable action on testing approaches. Implementing these strategies can help organisations improve software outcomes and maintain competitiveness in the evolving software development landscape.